1999
DOI: 10.1038/sj.ejcn.1600819
|View full text |Cite
|
Sign up to set email alerts
|

Milk hypersensitivity in young adults

Abstract: Objective: To estimate the prevalence of milk hypersensitivity in Finnish adults. Design: Cross-sectional study. Subjects: Two hundred men and 206 women aged 27 y randomly recruited from the population register in southwestern Finland. Interventions: The subjects were interviewed about their dairy product consumption, abdominal discomfort after dairy product intake and lactose intolerance. From serum samples, serum reactivity to milk protein and milk-speci®c IgG 1 , IgG 2 , IgG 3 and IgA were measured. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 27 publications
6
28
0
2
Order By: Relevance
“…Consistent with this, Pelto et al [11] have shown that hypersensitivity to cow's milk does also occur in adults but the mechanism is most likely not milk-specific antibody-mediated but rather due to an increase in serum reactivity to milk protein. The level of IgG decreased according to the age statistically significantly.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Consistent with this, Pelto et al [11] have shown that hypersensitivity to cow's milk does also occur in adults but the mechanism is most likely not milk-specific antibody-mediated but rather due to an increase in serum reactivity to milk protein. The level of IgG decreased according to the age statistically significantly.…”
Section: Discussionsupporting
confidence: 57%
“…In this study we did not have the opportunity to measure milk-specific IgG4. However, the results of the earlier studies conducted in adults provided controversial results [9][10][11][12][13] .…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Os resultados obtidos por Verwimp et al (1995) e Pelto et al (1998), mostram que indivíduos alérgicos a proteína do leite e intolerantes a lactose formam grupos distintos, ou seja, os alérgicos a proteína do leite de vaca, geralmente não são intolerantes à lactose. Apesar da alergia a proteína do leite ser considerada uma doença principalmente de crianças, Pelto et al (1999) estimaram prevalências entre 3 a 6% da população adulta na Finlândia.…”
Section: Alergiaunclassified
“…Further, allergy to cow's milk may induce gastrointestinal symptoms in children [4Á6]. Hypersensitivity to milk, however, may occur in adults also, as has recently been reported in, for example, Australia [7] and Finland [8,9], and hence may be one reason for milk-related gastrointestinal problems.…”
mentioning
confidence: 99%